1990
DOI: 10.1246/bcsj.63.1447
|View full text |Cite
|
Sign up to set email alerts
|

The Raman Spectral Study on the Solution Structure of Iron(III)-edta Complexes

Abstract: The Raman spectra of iron(III) complexes with ethylenediaminetetraacetate were observed for the purpose of elucidating the structure of the complexes in solution. In a Raman spectral study on the solid complexes, the spectra in the 300–600 cm−1 region were found to be diagnostic to coordination geometry. Namely, the coordination number can be determined on the basis of the wavenumber difference of the two major bands observed in the 450–600 cm−1 region; the wavenumber differences observed for heptacoordinate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…If this assignment is correct, the simple rule that an increasing coordination number results in increasing isomer shift, which seems to work for momoneric species, [32] would not work when going from monomer to dimer [Equation (2)]. This isomer shift implies sixfold coordination, which would be in agreement with the suggestion of Kanamori et al, [34] who claim that one carboxylate on each Fe center is dechelated. On the other hand, the driving force for dechelation could be a tendency to gain a more symmetrical (closer to octahedral) and therefore energetically favorable structure for the ligand sphere of iron, which would certainly result in a low quadrupole splitting.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…If this assignment is correct, the simple rule that an increasing coordination number results in increasing isomer shift, which seems to work for momoneric species, [32] would not work when going from monomer to dimer [Equation (2)]. This isomer shift implies sixfold coordination, which would be in agreement with the suggestion of Kanamori et al, [34] who claim that one carboxylate on each Fe center is dechelated. On the other hand, the driving force for dechelation could be a tendency to gain a more symmetrical (closer to octahedral) and therefore energetically favorable structure for the ligand sphere of iron, which would certainly result in a low quadrupole splitting.…”
Section: Resultssupporting
confidence: 72%
“…[33] Note that the quadrupole shift of A2 may not be directly related to quadrupole splitting data obtained from Lorentzian fits of nonmagnetic species because the relative orientation of the electric field gradient and the magnetic field is not known. We note here that Kanamori et al [34] have found hexacoordinate Fe III -EDTA species in solution only at even lower pH (in 1-2  HCl) using Raman spectroscopy, while at pH 1.2 they identified heptacoordinate species. The presence of chloride vs. nitrate anions (the latter in our case) may have some significance in this discrepancy.…”
Section: Resultsmentioning
confidence: 47%
“…10 However, from the literature data, Fe-OH 2 vibrations of Fe H 2 O 6 3C entities 11 and (Fe-O-Fe) or (Fe-OH-Fe) vibrations of dimeric species 12,13 could also range between 450 and 550 cm 1 , leading to attribution difficulties. IR bands of bis(glycinato) complexes observed in the 440-550 cm 1 and 290-415 cm 1 ranges were attributed to (M-N) and (M-O) vibrations, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2,30 Because of the manifold ways EDTA is used on a daily basis, it is important to investigate the structural and dynamical properties of EDTA complexes in the aqueous medium. In fact, many studies have been carried out so far to characterise metal chelating EDTA in the solid 5,[10][11][12][13][14][15][18][19][20]23,31 and liquid phase [6][7][8][9]16,17,[20][21][22]24,25,32 using a number of different experimental methods including NMR, IR/RAMAN, X-RAY and EXAFS/XANES spectroscopy. It was concluded that the coordination behaviour of EDTA strongly depends on the nature of the complexed metal as well as on the pH value of the medium.…”
Section: Introductionmentioning
confidence: 99%